Chronic obstructive pulmonary disease - C. Whittaker (South African Family Practice)
Chronic obstructive pulmonary disease affects millions of people, has a major impact on quality of life and has become an important cause of death worldwide. Over the past decade, a better understanding of COPD has been gained, while research into new therapies and treatment strategies has provided significant treatment advances. In this article, the different therapeutic classes that are available for COPD will be reviewed, including combination therapy and the recommended stepwise approach for disease management.